Human Capital and Social Capacity of the Regional Space of Arctic Karelia - Alexander D. Volkov; Aleksandr O. Averyanov; Natalia A. Roslyakova; Polina A. Golomydko (Арктика и Север)
The development of the Russian Arctic in the strategic perspective will require the attraction of significant labor resources. However, currently the population outflow trends prevail. The creation of territorial conditions for the expanded reproduction of human capital is of crucial importance in this context. The purpose of the study is to identify the territorial specificity of the conditions for the reproduction of human capital in Arctic Karelia in aspects reflecting the social capacity of the territory. The first task is to study the territorial conditions of human capital reproduction related to its social aspect: health care system, education system, culture, leisure and entertainment. The second task is to assess the possibility of applying the concept of social capacity of space to study the social component of the conditions of human capital reproduction. Complex economic and sociological tools are used. Information bases: Rosstat data, SPARK data, results of the population survey (autumn 2023). A comparative analysis of spatial aspects of the distribution of conditions for the reproduction of human capital and population estimates was carried out. According to the population’s estimates, the most important problems in the health care sector are the shortage of specialists, lack of modern equipment, inaccessibility of complex types of medical care and a narrow range of laboratory tests. The key problems in the field of education are lack of specialists and institutions of higher professional education, decline in the level of education and poor condition of school buildings and kindergartens. The conclusion is made about the structure of indicators of the pro-spective concept of social capacity of territories and the necessary addition of information bases in accordance with its conceptual logic. The practical significance of the research lies in the formation of analytical bases for ensuring the expanded reproduction of human capital in the territories of the Russian Arctic.